Association of clinical-morphological and molecular-genetic factors (mutations in GNAQ and GNA11 oncogenes and АBСB1 gene polymorphism) in patients with iris melanoma - S. V. Saakyan; I. V. Svirina; A. Yu. Tsygankov; A. M. Burdennyi; V. I. Loginov (Российский офтальмологический журнал)
Purpose: to analyze the frequency of GNAQ/GNA11 mutations in circulating tumor DNA and tumor tissue, and the frequency of genotypes of polymorphic marker C3435T of ABCB1 gene in patients with iris melanoma. Material and methods. The study included 139 patients with uveal melanoma (UM) followed in 2011–2023. The experimental group included 46 patients with iris melanoma (n = 20, group I) and ciliary body involvement (n = 26, group II), who underwent a molecular genetic study. The comparison group III consisted of 30 UM patients managed in 2012. Morphologically, uveal melanoma was verified in all cases. Results. No mutations in the GNAQ/GNA11 genes were identified in group I. In group II, one heterozygous mutation in the GNAQ/GNA11 genes was detected in 2 patients (7.7 %). No significant associations with clinical or pathomorphological features were found (p > 0.1). In the comparison group III, mutations in the GNAQ/ GNA11 genes were detected in 27 patients (90 %). When comparing the frequency of heterozygous mutations in the GNAQ/ GNA11 genes significant differences between the experimental groups and the comparison group were revealed (F = 0.0000001, χ2 = 56.45). The CC genotype of the C3435T polymorphic marker of the ABCB1 gene was found in 90 % (F = 0.026418, χ2 = 5.36, significantly more frequently than in group III), in group II — in 92.3 % (F = 0.006183, χ2 = 7.75, significantly more frequently than in group III), in group III it was found in 60 %. The TT genotype was not detected in any group. Conclusion. This study has shown that the frequency of mutations in GNAQ and GNA11 genes, the frequency of CT genotype of ABCB1 polymorphic marker C3435T gene in iris melanoma is significantly lower than that in choroid melanoma, indicating a relatively favorable tumor behaviour.